A Low-Cost and Fast Real-Time PCR System Based on Capillary Convection. (February 2017) - Qiu, Xianbo; Ge, Shengxiang; Gao, Pengfei; Li, Ke; Yang, Yongliang; Zhang, Shiyin; Ye, Xiangzhong; Xia, Ningshao; Qian, Shizhi
A low-cost and fast real-time PCR system in a pseudo-isothermal manner with disposable capillary tubes based on thermal convection for point-of-care diagnostics is developed and tested. Once stable temperature gradient along the capillary tube has been established, a continuous circulatory flow or thermal convection inside the capillary tube will repeatedly transport PCR reagents through temperature zones associated with the DNA denaturing, annealing, and extension stages of the reaction. To establish stable temperature gradient along the capillary tube, a dual-temperature heating strategy with top and bottom heaters is adopted here. A thermal waveguide is adopted for precise maintenance of the temperature of the top heater. An optimized optical network is developed for monitoring up to eight amplification units for real-time fluorescence detection. The system performance was demonstrated with repeatable detection of influenza A (H1N1) virus nucleic acid targets with a limit of detection of 1.0 TCID50 /mL within 30 min.